Oxidative stress in Microcystis aeruginosa as a consequence of global climate change - Hernando, Marcelo (2016)
Cyanobacteria are phototrophic organisms with great ecological and economical importance.Species of the genus Microcystis are known for their potential ability to synthesize toxins, notably microcystins.There is a growing interest in the evaluation of oxidative stress in relation to the impact of global climate change on natural ecosystems in different trophic levels. Several studies have focused on the analysis of organismal responses to mitigate the damage by controlling the generation of reactive oxygen species. Variations in environmentalfactors caused by climate change generate a situation of oxidative damage in Microcystis aeruginosa as a direct or indirect consequence. In this study we evaluate the effects of ultraviolet radiation and temperature on physiological and biochemical responses of a native M. aeruginosa (strain CAAT 2005-3). The results from the exposure to ultraviolet radiation doses and temperature changes suggest a high ability of M. aeruginosa to detect a potential stress situation as a consequence of reactive species production and to rapidly initiate antioxidant defenses. Increased catalase activity is an antioxidant protection mechanism in M. aeruginosa for short and long term exposure to different changes in environmental conditions. However, we found a ultraviolet-B radiation threshold dose above which oxidative stress exceeds the antioxidant protection and damage occurs. In additionour results are in agreement with recent findings suggesting that microcystins may act as protein-modulating metabolites and protection against reactive oxygen species.It is concluded that cyanobacteria have adaptative mechanisms that could lead to the replacement of species highly susceptible to oxidative stress by others with a higher system of antioxidant protection.